Evaluation of fms, dynamic balance and jump performance in faculty of sports sciences students - Gamze Erikoglu Orer; Seyfullah Celik; Burak Alperen Unsal; Busra Yilmaz; Ipek Akinci; Salih Cabuk (Ozlem Book Center, 2023)
The aim of this study was to investigate whether there is a difference between the Functional Movement Screening (FMS), dynamic balance and drop jump values of male and female athletes and non-athletes. 41 athletes (23 male and 18 female) and 27 non-athletes (14 male and 13 female) participated in this study. FMS, Y balance, 40 and 50 cm drop jump tests values of participants were collected, respectively. Data were analyzed by using SPSS 22.0 statistical program. Two Independent Samples t-test was used to analyze the differences between groups. Comparisons of athlete male-female groups demonstrated significant differences in terms of FMS, 40-50 cm height, flight times, power, Reactive Strenght Index (RSI) and 50 cm ground contact times, that of non-athlete male-female indicated significant differences in regard to right leg Y Balance Test Composite Scores, 40-50 cm jumping height, flight times, power and RSI values. Moreover, there are significant differences in terms of FMS scores in athlete-nonathlete female groups (p<0.05). Regardless of sportiveness, significant differences were found in 40-50 cm jumping height, flight times, power, RSI, contact times between genders. FMS scores can serve as a guide for long-term athlete development and injury prevention programs.